Marketing Of Islamic Education Institutions Of Services - Nurul 'Aini, Robi'ul Afif (Ats-Tsaqofi: Jurnal Pendidikan dan Manajemen Islam, 2021)
The development of technology in the era of industrial relovation 4.0 brings convenience and shifts in various things, one of which is that educational institutions are required to be able to compete properly in meeting or even exceeding the wants and needs of society as users of educational services by making continuous improvements in all aspects of education to improve quality and quality of education. Educational institutions are understood as a production organization that produces educational services purchased by consumers. Products in the context of madrasah education services are services offered to customers in the form of reputation, prospects, and a variety of choices. Marketing of educational services is a strategy to improve the quality of education which is the most important element for the quality and progress of the level of education in an educational institution. Educational institutions that are able to survive and be able to win the competition for educational services are institutions that can offer a reputation, prospects, good quality education, and bright opportunities for students to make the choices they want. Marketing, which is used specifically in schools, is the analysis, planning, implementation and control of carefully formulated programs designed to generate voluntary exchange of values ​​with the target market / target market for educational services to achieve school goals.